THE IMPORTANCE OF PROJECT-BASED LEARNING IN TEACHING ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article deals with the problem of teaching English in Higher education. It studies the importance of project-based learning in teaching process and the ways of using this type of learning in teaching English.